Modification of squash (Cucurbita pepo) candy bar by peanut (Arachis hypogaea) incorporation - Gabayeron, RD Cabillo (2006)
Four formulations of squash-peanut candy bars were prepared by varying the ratio of peanuts to squash: 1:1 (F1), 1:2 (F2), 1:3 (F3) and 1:4 (F4).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Squashes; Peanut; Candy bar